IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE APPLICATION OF PROBLEM-BASED LEARNING MODEL FOR GRADE XI STUDENTS AT UPT SMA NEGERI 1 MAROS - Nurmianti; Munirah (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This study aims to improve students’ mathematics learning outcomes on Matrix material. This type of research is a classroom action research with two cycles carried out at UPT SMA Negeri 1 Maros in the odd semester of the 2022/2023 academic year. The research subjects were students of class XI MIPA 4 UPT SMA Negeri 1 Maros. The research instruments used were learning devices, evaluation sheets, and observation sheets. The data collection technique in this study was by observation in the form of observation sheets and tests given to the research subjects. In this study, the Quantitative Descriptive Analysis technique was used. Based on the data analysis, the results showed that by using the Problem Basic Learning model on Matrix material there was an increase in student learning outcomes from an average of 92.54 in the initial test to 92.71 in the first cycle and increased to 92.74 in the second cycle with a percentage of 100% completion in the initial test and both cycles. In addition, there was also an increase in student activity in the student activity component from 83.33% in the initial test to 91.67% in cycle I and then increased to 100% in cycle II. In the student attention component from 83.33% in the initial test and cycle I, then increased to 91.67% in cycle II. In the student discipline component from 83.33% in the initial test, and consistently 83.33% in cycle I, then increased to 100% in cycle II. In the student assignment component from 75% in the initial test to 83.33% in cycle I and then increased to 91.67% in cycle II.